Spatial Reaction of Prices in the Vegetable Markets to Restrictions on Foreign Trade - Anna Vladimirovna Stupnikova (Prostranstvennaâ Èkonomika, 2018)
The paper presents an assessment of the change in the spatial differentiation of vegetable prices in conditions of imposing restrictions on foreign trade. The purpose of the study was to identify the specifics of price reactions in the regional vegetable markets to the ban on foreign economic operations with Turkey, that require the import of certain types of Turkish vegetables into the Russian Federation. The method of research included three stages. In the first stage, using the volatility indicator, the spatial behavior of vegetable prices was assessed; in the second – the groups of vegetable markets of the subjects of the Russian Federation were determined, characterized by the greatest price differentiation, for which the border effect was calculated in the third stage of the study. The study was conducted for two time periods: 2015 (before the ban on the import of vegetables from Turkey) and January – October 2016 (the period of the ban on the import of vegetables from Turkey). A comparative evaluation of the results of the study for two study periods showed that in January – October 2016, the range of variation and the mean value of the relative CPI volatility for vegetables decreased. In addition, border effects have decreased for all selected groups of markets, characterized by increased differentiation of prices for vegetables. Based on the results obtained, a conclusion was made that the spatial differentiation of prices in regional vegetable markets in January-October 2016 has reduced compared to 2015, which indicates the adaptation of regional vegetable markets to changes in institutional conditions